None greater : the undomesticated attributes of God - Barrett, Matthew, 1982- (Grand Rapids,MI Baker Books, a division of Baker Publishing Group, 2019)
"Author and theologian helps readers get to know a God who is much bigger than we ever imagined by explaining his attributes in a way that highlights their relevance and impact on the Christian life"--
Includes bibliographical references (pages 273-283)
Keywords: God (Christianity) -- Attributes